(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The digital transformation wave is reshaping governance and economic frameworks worldwide. Uzbekistan and Turkey have embarked on strategic cooperation to foster digital economy growth and implement e-government projects that enhance public service delivery and economic integration. This article explores the scope, impact, and challenges of their bilateral cooperation in digital economy initiatives and e-government projects. By analyzing government reports, policy documents, and academic sources, the study highlights how technology transfer, joint ventures, and knowledge exchange between the two countries are driving innovation in Uzbekistan’s public sector and digital infrastructure. The findings reveal that while significant progress has been made, areas such as cybersecurity, digital literacy, and infrastructure require continuous attention to sustain development.